Phylogeny and biogeography of the genus Piezura Rondani (Diptera: Fanniidae) - Wang, Ming-Fu; Zhang, Dong; Ao, Hu (Zootaxa, 2010)
The Holarctic genus Piezura Rondani (Diptera, Fanniidae) is reviewed. Phylogenetic relationships among the species in this group, as well as the biogeography of these species, are discussed on the basis of a cladistic analysis. Piezura graminicola shanxiensis Xue, Wang and Wu, 1998 is redescribed and elevated to species rank based on comparison of its morphology and phylogenetic relationships. Syllegopterula flava Hsue, 1983 and its replacement name Thricops flavidus Xue, 1998 are treated as junior synonyms of Piezura graminicola (Zetterstedt, 1846).